The influence of Hotel Image on Satisfaction Customer at Penginapan Oyo - Muhammad Jahid Lilhaq; Ahmad Nuh; Achmad Tifazza Alfarizi (Penerbit Hellow Pustaka, 2024)
This research aims to investigate the influence of the hotel image on satisfaction customer at penginapan oyo accommodation. This research uses a quantitative approach using a questionnaire distributed to visitors staying at various Oyo accommodations. The research sample consisted of 105 respondents selected randomly. Data analysis was carried out using a simple linear regression technique to test the relationship between hotel image variables and customer satisfaction. The research results show that hotel image has a significant influence on customer satisfaction at Oyo accommodation. Hotel image variables, such as cleanliness, service quality, available facilities, and comfort, positively contribute to customer satisfaction. These findings highlight the importance of hotel management paying attention to and improving their image in an effort to increase customer satisfaction. The practical implication of this research is that Oyo accommodation can strengthen their image through investing in aspects identified as important for customer satisfaction, thereby increasing their customer loyalty and satisfaction. This research provides a better understanding of the factors that influence customer satisfaction in the hospitality industry, particularly at Oyo Inns, and provides guidance for practitioners to improve the quality of their services and customer experience